Perancangan dan Pembuatan Media Pembelajaran Berbasis Android pada Mata Pelajaran Iqra - Jhon Veri; S Surmayanti; Silfia Andini (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2020)
This study aims to see the validity, practicality and effectiveness of designing and making Android-based learning media in Iqra subjects for early childhood / kindergarten students in Padang. This study uses a research development method (Research & Development). The research subjects may be 10 people. This research method uses a model (ADDIE), with the design and development steps as follows. (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The results of the validity test by the experts as a whole amounted to 93.93%, so the level of validity that can be interpreted is very valid to use. The overall test result was 89.42%, so that the level of practicality could be interpreted as very practical to use. The results of the effectiveness trial were 85.98% so that the effectiveness level could be interpreted effectively. In conclusion, the decisions and expert input as well as the results of field trials of Android-based learning media as learning media have been tested for feasibility, excellence, and can be used in the learning process in the Iqra subject for PAUD / Kindergarten students in Padang.